Patstāvīgās vārdšķiras formālā latviešu valodas analīzē - Saulīte, Baiba; Nešpore, Gunta (Baltistica, 2012)
CONTENT WORDS IN THE FORMAL ANALYSIS OF LATVIANSummaryTo characterize morphological features of each word in a text, a set of morphological features for Latvian has been defined. It describes grammatical categories and their possible values characteristic of a particular part of speech or a smaller group of words.To define this set it was necessary to clarify several grammatical categories of content words due to fact that their description in the existing grammars of Latvian differs or is not sufficiently explicated.Morphological features of pronouns and verbs are discussed in detail.Regarding pronouns, the main issues are the nominal categories (gender, number and case) and the category of person. A table with a full list of Latvian pronouns and their grammatical categories is offered.Regarding verbs, the problematic categories are tense (for debitive and conditional forms) and person (for debitive, relative and conditional forms), as well as the category of number for the third person verbs.
Keywords: Latvian; content words; formal language analysis; computer linguistics; morphology